Weaving webs of connection: Empathy, perspective taking, and students’ motivation - Henry, Alastair; Thorsen, Cecilia (Studies in Second Language Learning and Teaching, 2019)
L2 motivation is a relational phenomenon, shaped by teacher responsiveness (Lamb, 2017; Ushioda, 2009). Little, however, is known about the practices in which responsiveness is manifested. Drawing on research from the culturally responsive teaching paradigm (Petrone, 2013), and highlighting the role of empathy and perspective taking (Warren, 2018), the aim of this ethnographic case study of two lessons with a focus on poetry is to develop a relational understanding of the evolution of motivation. Analyses reveal how perspective taking has instructional and interactional dimensions, and how connections between lesson content and funds of knowledge with origins in students’ interactions with popular culture bring additional layers of meaning to learning. It is suggested that while connections that arise through perspective taking practices shape students’ in-the-moment motivational responses, they also accumulate in ways that lead to enduring motivational dispositions.